Algoritma Genetika Untuk Penjadwalan Karyawan Ira Stationary - Kurniasari Abram; Novianita Achmad; Muhammad Rezky Friesta Payu; Nurwan Nurwan; Djihad Wungguli; Asriadi Asriadi (Universitas Negeri Gorontalo, 2023)
Employee scheduling is an activity plan for time sharing that contains a schedule for carrying out planned activities in the form of a table. This study aims to create an employee schedule model using a Genetic Algorithm, which is a heuristic method inspired by the process of natural selection, the strong will survive and reproduce, the stages of the Genetic Algorithm are population initialization, fitness value, selection, crossover, and mutation. The study results show an optimal model consisting of at most two shifts with a maximum of two holidays a week and not consecutively.